BUILDING A COMMUNITY ECONOMY IN PROCESSING PATIN FISH INTO SHREDDED FISH - Wahyuddin Bakri; Abd Wahidin; Andi Zulfayani; Anggi Yus Susilowati; Vina Alfyunita (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
Building a social economy is an effort to alleviate poverty in society, by providing knowledge and skills to the community, one of the efforts made is providing training in managing the assets and potential that exist in Tajuncu village, Soppeng Regency. This PKM activity aims to provide understanding and skills to the community in Tajuncu village about processing Patin fish and marketing Shredded Patin fish products. PKM activities use the ABCD approach to find assets or potential natural resources that exist in the community and its environment. Based on the aim of the PKM activity, to produce knowledge of Patin fish processing skills in the form of shredded Patin fish products, to follow up on these shredded products, then continue by providing understanding and skills in marketing shredded Patin fish products, so that the processed products can be marketed both locally and nationally